Dopamine synthesis and dopamine receptor expression are disturbed in recurrent miscarriages. Issue 5 (May 2018) - Gratz, Michael J; Stavrou, Stavroula; Kuhn, Christina; Hofmann, Simone; Hermelink, Kerstin; Heidegger, Helene; Hutter, Stefan; Mayr, Doris; Mahner, Sven; Jeschke, Udo; Vattai, Aurelia
Abstract : Objectives: l -dopa decarboxylase (DDC) is responsible for the synthesis of dopamine. Dopamine, which binds to the D2 -dopamine receptor (D2R), plays an important role in the maintenance of pregnancy. Aim of our study was the analysis of DDC and D2R expression in placentas of spontaneous miscarriages (SMs) and recurrent miscarriages (RMs) in comparison to healthy controls. Methods: Patients with SM (n = 15) and RM (n = 15) were compared with patients from healthy pregnancies (n = 15) (pregnancy weeks 7–13 each). Placental tissue has been collected from SMs and RMs from the first trimester (Department of Gynaecology and Obstetrics, LMU Munich) and from abruptions (private practice, Munich). Placental cell lines, BeWo- and JEG-3 cells, were stimulated with the trace amines T0 AM and T1 AM in vitro . Results: Levels of DDC and D2R in trophoblasts and the decidua were lower in RMs in comparison to healthy controls. Stimulation of BeWo cells with T1 AM significantly reduced DDC mRNA and protein levels. Via double-immunofluorescence, a DDC-positive cell type beneath decidual stromal cells and foetal EVT in the decidua could be detected. Conclusions: Downregulation of DDC and D2R in trophoblasts of RMs reflects a reduced signal cascade of catecholamines on the foetal side.